Spectrum of seizure disorder in children between 1-18 years age at a tertiary care hospital: a longitudinal study - Himanshu Dua; Dr. Anjali Edbor; Seher Kamal (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: To study the spectrum of seizures and types of anti-epileptic drugs in various types of seizures in children.Methods: A hospital based longitudinal study was conducted in the department of Pediatrics over two-years of period. A total of 161 cases presenting with seizures were studied for clinical features, imaging studies, EEG and pharmacotherapy given for various types of seizures (Monotherapy / combination therapy).Results: In the present study, the patient’s age ranged from 1year to 18 years. There were 72 (44.7%) females and 89 (55.2%) males. The male to female ratio was 0.8. Investigation like EEG, neuroimaging which included MRI / CT SCAN BRAIN were done. Out of 161 cases, EEG was done in all the cases, 89.44% (144) had EEG abnormality. 11% (17) presented with no EEG abnormality and MRI was done in 80.21% (129), out of which 53.48 % (68) were abnormal, CT scan was done in 19.87 % (32) of which 21.87% (7) were abnormal. Maximum used pharmacotherapeutic agent was sodium valproate (46.3 %) for generalised tonic clonic (GTCS) and minimum was combination of 3 anti-epileptic drugs (7%).Conclusion: Seizures in children are a common indication for hospital admission. They can be provoked or unprovoked. Early detection of the cause of seizures helps in instituting appropriate treatment. Children with seizures should be on regular long term follow up and treatment and proper response to therapy should be evaluated. Evaluation of the type of seizure with specific EEG findings helps in early and appropriate initiation of AED.